Antioxidant agents in wartime: prospects for the development of new biologically active compounds based on 1,2,4-triazole derivatives - K. K. Isaycheva; A. G. Kaplaushenko; Yu. G. Sameliuk; O. P. Shmatenko; A. M. Solomennyi (Український журнал військової медицини)
Introduction. This article presents an analysis of the antioxidant activity of 4-amino-5-(2-, 3-, 4-nitrophenyl)-1H-1,2,4-triazole-3-thiones and their synthetic analogues, 5-(4-methoxyphenyl, 3,4,5-trimethoxyphenyl)-1,2,4-triazole-3-thiones and their synthetic analogues, and 5-(quinolin-2-yl, 2-hydroxyquinolin-4-yl)-4-R1-1,2,4-triazole-3-thiones. The main conclusions drawn from these studies are as follows: